Intrinsic wettability of graphitic carbon. (June 2015) - Wei, Yuanyang; Jia, Charles Q.
Abstract: The wettability of graphitic carbon can impact the behavior of many carbonaceous materials in a variety of systems involving water, for example, the carbon aerosols–cloud interaction that affects the climate and the penetration of micropores by aqueous solution in activated carbons. Previous studies on this topic have been limited to the basal surface of graphite. Apparent water-contact angle (WCA) values reported in the literature for the basal surface of graphite or graphene sheet vary from 35° to 126°, due to factors such as surface contamination and roughness. The intrinsic wettability of graphitic carbon remains uncertain. Here we report the first experimental attempt of quantifying the intrinsic wettability of the edge surface of graphite. We show that the basal surface is intrinsically hydrophilic with a WCA of about 61°; the edge surface is more hydrophilic than the basal surface and has an intrinsic WCA likely less than 40°. We also show that the apparent WCA is highly sensitive to sample preparation procedures. Annealing, a commonly used method for removing surface organic contaminants, could result in an underestimated WCA due to oxidation by the trace O2 in the inert gases.